Analisis Persepsi Masyarakat Terhadap Purchase Intention Kendaraan Listrik Dengan Metode SEM - Gani, Muhammad Yusuf Syahputra; K, Iwa Garniwa Mulyana (ENERGI & KELISTRIKAN, 2024)
A power source is required for transportation. Currently, fossil energy remains the dominant form of energy demand in transportation. However, with the depletion of fossil energy resources and the increasing demand for energy due to population growth, it is possible to meet energy demand in almost every country in the world, including Indonesia, where the supply of natural resources, i.e. fossil energy, as an energy source is threatened. is the challenge. Oil for transportation is on the decline. Although the transport sector has only grown by 4.5% of the country’s GDP, the sector is also an important economic driver. In this study, research methods using specific populations or samples are used, sampling procedures are usually random, data collection is done using instrumental studies, and data analysis is done with the purpose of testing established hypotheses. It is done quantitatively or statistically. Multivariate structural equation model (SEM) analysis was used to test the hypotheses of this study. The hypothesis advanced in this study is that environmental awareness does not significantly affect purchase intention, but perceived ease of use, perceived value for money, and perceived usefulness have positive and significant effects on purchase intention. suggests that it has a significant impact. Judging by the results of the analysis, the value of incentives provided by the state to its citizens in the form of subsidies for the purchase of electric motorcycles is reasonable. This is reflected in the public’s high regard for the acceptability of price adjustments, which must also consider the quality gained by purchasing an electric vehicle. It can also be analyzed in terms of the impact of value on perceived money on an individual’s decision to purchase an EV.